Impact of Work-From-Home Human Resource Practices on the Performance of Online Teaching Faculty During Coronavirus Disease 2019 - Irshad, Huda; Umar, Khawaja Muhammad; Rehmani, Mahmood; Khokhar, Munnawar Naz; Anwar, Naveed; Qaiser, Ayaz; Naveed, Rana Tahir (Frontiers in Psychology, 2021)
The purpose of this study was to investigate the impact of work-from-home human resource practices on faculty’s performance and that too under the drastic circumstances of COVID-19. The population of the study included faculty members of the higher education institutions in Sialkot, Pakistan. The study filled the gap of scarce literature on the impact of various human resource practices by human resource officials while working from home during lockdown observed to reduce the spread of COVID-19. Based on reinforcement theory, this article proves that there is a significant relationship between human resource practices (including training, performance appraisal, career planning, employee participation, job definition, compensation, and selection) and faculty performance. It also proves that there is a strong positive relationship between the two variables. The findings of this study provide a blueprint to improve human resource practices for high performance by faculty in the higher education sector during work-from-home settings.